Two new species of Begonia (Begoniaceae) from Aurora Memorial National Park, Luzon Island, Philippines - Ang, Yu Pin; Collantes, John Paul R.; Mansibang, Jayson; Cruz, Cyrus Job P. Dela; Aumentado, Jamie Ann M.; Bimeda, Shane B.; Callado, John Rey; Fritsch, Peter W.; Bustamante, Rene Alfred Anton (Phytotaxa, 2023)
Begonia masilig and Begonia akaw, both endemic to Aurora Memorial National Park, Luzon, Philippines, are described as species new to science. Begonia masilig is similar to B. droseroides in its rhizomatous habit and glandular trichomes on the inflorescence, but differs in lamina shape and overall size, and the vestiture of stipule, lamina margin, and outer tepals of staminate flowers. Begonia akaw is similar to B. ramosii in its short erect habit, ovate lamina and congested terminal inflorescence with 2-tepaled staminate flowers, but differs in inflorescence size and arrangement, and bract and ovary shape. Both new species are here proposed to be Endangered (EN) as per IUCN criteria.